2019
DOI: 10.1029/2019jb017577
|View full text |Cite
|
Sign up to set email alerts
|

Coda Wave Interferometry for Accurate Simultaneous Monitoring of Velocity and Acoustic Source Locations in Experimental Rock Physics

Abstract: In many geoscientific, material science, and engineering applications it is of importance to estimate a representative bulk seismic velocity of materials or to locate the source of recorded seismic or acoustic waves. Such estimates are necessary in order to interpret industrial seismic and earthquake seismological data, for example, in nondestructive evaluation and monitoring of structural materials, and as an input to rock physics models that predict other parameters of interest. Bulk velocity is commonly est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…This wavelet represents the transducer response to the first arrival rather than the P-wave coda used by previous studies (eg. Scuderi et al, 2016;Singh et al, 2019), which represents accumulated effects of multiple reflections through frictional interfaces and the bulk ( Figure 4 in Tinti et al, 2016). For more detailed experimental methods, we refer readers to Shreedharan et al (2019) and Supporting Information S1.…”
Section: Methodsmentioning
confidence: 99%
“…This wavelet represents the transducer response to the first arrival rather than the P-wave coda used by previous studies (eg. Scuderi et al, 2016;Singh et al, 2019), which represents accumulated effects of multiple reflections through frictional interfaces and the bulk ( Figure 4 in Tinti et al, 2016). For more detailed experimental methods, we refer readers to Shreedharan et al (2019) and Supporting Information S1.…”
Section: Methodsmentioning
confidence: 99%
“…Application of a similar approach to detect changes in source location was found to be very accurate, provided the displacement divided by the dominant wavelength did not exceed ~0.5, although follow-up work has demonstrated that this threshold can be extended. This study has recently been published (Singh et al 2019).…”
Section: Earthquake Seismologymentioning
confidence: 99%
“…Coda wave interferometry (CWI) has been employed as an alternative, being sensitive to small fluctuations in material properties (e.g. Singh et al, 2019;Snieder et al, 2002;Griffiths et al, 2018), including crack damage (Lamb et al, 2017) or degree of saturation (Grêt et al, 2006). The utilisation of CWI at active volcanic systems has not only tracked migrating seismic sources (e.g.…”
Section: Rock Failure and Volcano Stabilitymentioning
confidence: 99%
“…after the directly arriving phases, and, in laboratory scale rock samples comprises surface waves and waves that have repeatedly scattered (reflected within) the medium (Grêt et al, 2006;Singh et al, 2019). Where conventional approaches to measuring first arrivals are highly sensitive to local heterogeneities and thus may not accurately represent bulk material properties, CWI effectively samples the whole material multiple times, a process which provides a robust constraint of bulk properties and amplifies even very minor temporal changes compared to direct arrivals (Singh et al, 2019;Snieder et al, 2002;Hadziioannou et al, 2009;Griffiths et al, 2018). We identified velocity reductions during mechanical testing in both compression and tension, the magnitude of which is greater in more porous samples in UTS but appears independent of porosity in UCS (Fig.…”
Section: Signals Of Heterogeneous Materials Deformationmentioning
confidence: 99%